A cohort study of ultrasonic semi-quantitative scoring for the diagnosis of serology-negative rheumatoid arthritis - Jing Xu,; Yiran Gong,; Kaiyi Yang,; Yabin Fang,; Wenting Li,; Shuqiang Chen, (Archives of Rheumatology, 2024)
Objectives: This study aims to explore the value of ultrasonic semi-quantitative scoring in the diagnosis of seronegative rheumatoid arthritis (RA). Patients and methods: Between January 2018 and October 2023, a total of 411 patients (241 males, 170 females; mean age: 50.9±17.5 years; range, 18 to 87 years) were included. Of these patients, 296 were diagnosed with RA (including 131 with seronegative RA [SNRA] and 165 with seropositive RA [SPRA]) and 115 with non-RA disease. Ultrasound examination was performed on all patients with suspected RA, focusing on evaluation of synovial hypertrophy (SH), power Doppler (PD) signals, and bone erosion (BE) for three to six months. The ultrasonic joint semi-quantitative score was evaluated for the sensitivity and specificity of detecting seronegative RA. Results: The three indexes of SH, PD, and BE were not significantly different between the SNRA and SPRA groups (p=0.223, p=0.176; p=0.272, respectively). However, there were differences on the SH1, SH3, PD, and BE grades between the SNRA group and the non-RA group (p<0.001 for all); when serology was negative and when the highest scored joint met PD Grade ≥2 or BE Grade ≥2, it showed both high sensitivity (93.12%) and high specificity (91.30%) for the diagnosis of RA. Conclusion: Ultrasound combined with semi-quantitative scoring is of promising significance in the early diagnosis of SNRA patients.